Situs Lobu Dolok, Makam Kuno di Kawasan Padang Lawas Sekitar Abad ke-17 Masehi - Sukawati Susetyo (Balai Arkeologi Sumatera Utara, 2010)
AbstractAs a sacred tomb, Lobu Dolok is not maintained properly. This is because the tomb is situated on a hilltop. Although the sacred, none of people know who is buried and what the meaning of these remains. This article attempts to make an interpretation based on signs left by the form of inscriptions, statues of women and men as well as a relief of vulva.